Can non-swallowing function assessment predict nasogastric tube removal in patients with poststroke dysphagia? A clinical study - Li, Bingjie; Zhang, Tong; Zhao, Jun; Li, Pengkun; Wu, Zhangwei; Zhao, Shengjie (Frontiers in Neurology, 2023)
Objective: This study aimed to predict nasogastric tube (NGT) removal in poststroke dysphagia (PSD) patients by non-swallowing function assessment. Methods: 232 eligible patients were enrolled and performed rehabilitation. In our study, Fugl-Meyer of motor score (FMM) and National Institute of Health Stroke Scale (NIHSS) were used to measure the motor and overall nervous system function. Logistic regressions were used to investigate the effect of 15 pre-existing conditions on NGT removal in PSD patients after rehabilitation. Results: The results indicated the following: 1) 78% of all 232 included patients removed NGT, while 22% remained feeding tube dependent after the 4 weeks rehabilitation; 2) Compared with the group of NGT reserved, older, higher rate of intubated or tracheostomy, and more severe baseline functions were found in the group of NGT removal; 3) Age (odds ratio [OR],0.907; 95% CI, 0.859 to 0.957; P=0.000), difference of FMM score in 4 weeks rehabilitation (OR, 1.219; 95% CI, 1.145 to 1.299; P=0.00), and item 9 of NIHSS (OR, 0.488; 95% CI, 0.252 to 0.946; P=0.034) were revealed as predictors of NGT removal after rehabilitation; Conclusions: We established a predictive model in PSD patients by non-swallowing assessment, which enable to predict swallowing recovery from non-swallowing function.